If it's not what You are looking for type in the equation solver your own equation and let us solve it.
X2+14X+48=0
We add all the numbers together, and all the variables
X^2+14X+48=0
a = 1; b = 14; c = +48;
Δ = b2-4ac
Δ = 142-4·1·48
Δ = 4
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{4}=2$$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(14)-2}{2*1}=\frac{-16}{2} =-8 $$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(14)+2}{2*1}=\frac{-12}{2} =-6 $
| 1/3x-2=14 | | 2/9k-1/3=5 | | 6-h−1=3 | | 2x+5/6=x/18 | | (4n+19)+(2n+23)=180 | | 4=3+n/4 | | 6/h−1=3 | | 17x+18=16x | | X-13+4x=12 | | 2(x+4)^2-18=54 | | 12/204=8/x | | 52=35-n | | 6h−1=3 | | 2(x+2)+3(x+4)=x+5 | | -9k=-45 | | 65=3/4×c-7 | | 2(a+7)=8 | | 3x2-36=0 | | 9(x+3)=7x-2x+11 | | (3k+9)(k-7)=0 | | 4x-6-8=4+2x | | 7(h=3)=6(h-3) | | 10-2(x+3)=10(x+4)-15 | | 1/2(x+1)+3/4(x+4)=x+5 | | 5-3920x^-2=0 | | 9-4c=17 | | 11x+1=9x+17 | | 11x+1=9x+5 | | |3x-1|=|2x+3| | | (3n+21)+(2n+39)=180 | | 1/2(x+1)+3(x+4)=x+5 | | -12x+2(4x-3)=-14-3x |